2010
DOI: 10.1130/g31213.1
|View full text |Cite
|
Sign up to set email alerts
|

Follow the water: Connecting a CO2reservoir and bleached sandstone to iron-rich concretions in the Navajo Sandstone of south-central Utah, USA

Abstract: Concretions with thick, iron oxide-cemented rinds and lightly cemented, iron-poor sandstone cores are abundant within the Navajo Sandstone near the southeast fl ank of the Escalante anticline (Utah, United States). Previous workers suggested the spheroidal concretions as analogs for Martian "blueberries" (hematite concretions), and linked the origin of concretions and bleaching of the Navajo Sandstone to the buoyant rise of hydrocarbons toward anticlinal crests. We measured azimuths of 163 pipe-like (pipy), jo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
102
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 48 publications
(107 citation statements)
references
References 20 publications
(24 reference statements)
3
102
0
2
Order By: Relevance
“…12) argued that reducing, buoyant fluids transported iron for concretion growth. Loope et al (2010) pointed out that, in the Escalante region, there is unambiguous evidence of iron transport down-dip. The direction of iron transport was subparallel to that of modern groundwater flow.…”
Section: Settingmentioning
confidence: 96%
See 2 more Smart Citations
“…12) argued that reducing, buoyant fluids transported iron for concretion growth. Loope et al (2010) pointed out that, in the Escalante region, there is unambiguous evidence of iron transport down-dip. The direction of iron transport was subparallel to that of modern groundwater flow.…”
Section: Settingmentioning
confidence: 96%
“…The latter study concluded that the negative values were evidence for fluid evolution associated with precipitation of iron oxide or adsorption of isotopically heavy Fe on silicate mineral grains during fluid flow. Loope et al (2010) interpreted the rinded, iron oxide-cemented concretions in the Navajo Sandstone to be alteration products of siderite-cemented sandstone. They concluded that the precursor (siderite) concretions are late diagenetic features that precipitated at shallow depth.…”
Section: Settingmentioning
confidence: 97%
See 1 more Smart Citation
“…10B, 10C). The iron-oxide cements are the oxidized remnants of siderite cements that (because of degassing of CO 2 -rich fluids) preferentially formed in sandstone on the downflow sides of joints (Loope et al, 2010). These iron-rich cements make the sandstone that composes the southern walls more resistant to erosion, so sheeting joints with high curvature cap the southern walls (Fig.…”
Section: Laterally Confined Sheeting Joints: Interpretationmentioning
confidence: 99%
“…This has variously been attributed to bleaching by buoyant hydrocarbons and methane rich brine (Beitler et al, 2003(Beitler et al, , 2005Chan et al, 2000;Garden et al, 2001;Parry et al, 2004Parry et al, , 2009) and by dense CO 2 -charged brine containing methane or sulfide reductants (Loope et al, 2010(Loope et al, , 2011Potter-McIntyre et al, 2013;Wigley et al, 2012, Figure 6. (A) Bleached basal sandstones of the Entrada Sandstone hosting CO 2 charged fluids.…”
Section: Co2w55 Core Stratigraphymentioning
confidence: 99%